2013
DOI: 10.1016/j.cell.2013.08.006
|View full text |Cite
|
Sign up to set email alerts
|

Endogenous Nuclear RNAi Mediates Behavioral Adaptation to Odor

Abstract: Summary Most eukaryotic cells express small regulatory RNAs. The purpose of one class, the somatic endogenous siRNAs (endo-siRNAs) remains unclear. Here we show the endo-siRNA pathway promotes odor adaptation in C. elegans AWC olfactory neurons. In adaptation, the nuclear Argonaute NRDE-3, which acts in AWC, is loaded with siRNAs targeting odr-1, a gene who's down regulation is required for adaptation. Concomitant with increased odr-1 siRNA in AWC, we observe increased binding of the HP1 homolog HPL-2 at the o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
99
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(99 citation statements)
references
References 85 publications
0
99
0
Order By: Relevance
“…For example, in the process of odorant adaptation, activation of EGL-4 by ODR-1 is thought to induce the downregulation of ODR-1 (Juang et al 2013). Without independent GC partners, such a feedback regulation would affect other processes in which EGL-4 is involved.…”
Section: Discussionmentioning
confidence: 99%
“…For example, in the process of odorant adaptation, activation of EGL-4 by ODR-1 is thought to induce the downregulation of ODR-1 (Juang et al 2013). Without independent GC partners, such a feedback regulation would affect other processes in which EGL-4 is involved.…”
Section: Discussionmentioning
confidence: 99%
“…Here, we describe a novel role for RDE-4 in embryonic neuronal migration, which is consistent with previous observations that the generation of some somatic 22G-RNAs is dependent on RDE-4 ( Lee et al 2006;Gu et al 2009). Interestingly, RDE-4 has also been recently shown to participate in the production of endogenous 22G-RNAs required to mediate odor adaptation in adult animals (Juang et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, in addition to the defects in mut-7 and rde-2 mutants that contribute to germline non-disjunction, the animals also harbor defects that persist into later developmental stages, affecting fertility in adult males. Indeed, endogenous siRNAi defects in mut-7 have been correlated with odor adaptation in AWC neurons of adults [24]. We investigated the nature of the fertility defects in mut-7 and rde-2 mutant males, and we found that the males were capable of producing progeny when the hermaphrodite parent was unc (paralyzed), suggesting that mutant males are defective in movements that are required for effective mating (Table 3).…”
Section: Averagementioning
confidence: 99%